2018
DOI: 10.1074/jbc.ra118.003044
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mitochondria-generated reactive oxygen species in cells using multiple probes and methods: Potentials, pitfalls, and the future

Abstract: Reactive oxygen and nitrogen species (ROS/RNS) such as superoxide (O), hydrogen peroxide, lipid hydroperoxides, peroxynitrite, and hypochlorous and hypobromous acids play a key role in many pathophysiological processes. Recent studies have focused on mitochondrial ROS as redox signaling species responsible for promoting cell division, modulating and regulating kinases and phosphatases, and activating transcription factors. Many ROS also stimulate cell death and senescence. The extent to which these processes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 113 publications
(111 reference statements)
2
88
0
Order By: Relevance
“…Since the triphenylphosphonium ion (TPP + ) group of MitoSOX Red has been reported to interfere with mitochondrial membrane potential, we verified that neither mitochondrial membrane potential nor mitochondrial ROS were influenced by TPP + in our experimental setting (Figure S5C,D). Enhanced ROS generation within the mitochondria was further verified by observing the increased oxidation of Prx3, an endogenous marker for redox status (Figure E) . In addition, we observed that the level of intracellular ROS was increased upon p53 expression (Figure F).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Since the triphenylphosphonium ion (TPP + ) group of MitoSOX Red has been reported to interfere with mitochondrial membrane potential, we verified that neither mitochondrial membrane potential nor mitochondrial ROS were influenced by TPP + in our experimental setting (Figure S5C,D). Enhanced ROS generation within the mitochondria was further verified by observing the increased oxidation of Prx3, an endogenous marker for redox status (Figure E) . In addition, we observed that the level of intracellular ROS was increased upon p53 expression (Figure F).…”
Section: Resultssupporting
confidence: 59%
“…Enhanced ROS generation within the mitochondria was further verified by observing the increased oxidation of Prx3, an endogenous marker for redox status (Figure 2E). 35 In addition, we observed that the level of intracellular ROS was increased upon p53 expression ( Figure 2F). To avoid possible artifacts resulting from the DCF-DA dye, 37 H 2 O 2 production upon p53 expression was further examined by using another ROS probe, Amplex Red.…”
Section: P53-induced Mitochondrial Elongation Accompanies Defects Imentioning
confidence: 76%
“…For detection with DHE, the cells were incubated with 25 μM DHE for 30 min at 37°C [58]. DHE emission was recorded using flow cytometry with an Ex/Em of 488/575 nm [59,60]. Antimycin A (AA) was used as a positive control.…”
Section: Measurement Of Intracellular Rosmentioning
confidence: 99%
“…DHE is a redox-sensitive probe that has been widely used to detect intracellular superoxide anions. The superoxide anion (O· 2 ) reacts with DHE to form an oxidized product and leads to the enhancement of fluorescence [59,60].…”
Section: Measurement Of Intracellular Rosmentioning
confidence: 99%
“…Various methodologies have been developed to track or quantify ROS production in cells;, they can be classified mainly into four groups, with relation to the methodological approach applied, i. e. electron spin resonance (ESR) probes, fluorescent probes, genetic sensors or electrochemical methods. Each of these techniques suffers from some intrinsic limitations: low specificity and limited quantitative information have been questioned for the commonly used fluorescent probes ,. Expensive, high‐level research equipment and not trivial sample preparation are the main limitation of ESR methods, while the relevant time required for generation of a genetic tool is a strong drawback for genetic sensors.…”
Section: Figurementioning
confidence: 99%